Effects of different substrates on production of oyster mushroom in walling of syangja, Nepal - Regmi, Sudip; Puri, Chiranjibi (Research in Agriculture Livestock and Fisheries, 2022)
This research was conducted in Agriculture Development Resource Center, Syangja to determine the effectiveness of substrate for the production of oyster mushroom (Pleurotus ostreatus). Completely Randomization Design was used for this research with three replications in which five treatments (substrate) were used i.e.; rice straw, finger-millet straw, saw dust, maize straw and maize cob. Days required for full colonization, first fruiting, harvesting time, total mushroom production, mushroom pileus diameter, and stipe length were observed by taking 5 sample randomly from each treatment. Among the investigated substrate compositions, maize cob required the fewest days (19 days) to complete spawn running, followed by finger-millet straw (21 days), while saw dust required the most days (38 days) to complete spawn running. Finger-millet straw indicated the shortest time (28 days) harvesting, and the maximum yield was found in finger-millet straw (1.05 kg) and highest stipe length (5.3cm) was found in saw dust followed by rice straw (4.8 cm). Among various used substrate finger-millet straw was found to be the best for mushroom production at least in Waling, Syangja. Res. Agric., Livest. Fish.9(1): 11-16, April 2022